2022
DOI: 10.1002/aenm.202103556
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Energy Manifold of Quasi‐Two‐Dimensional Perovskites for Efficient Carrier Extraction

Abstract: Harvesting the excess energy from absorbed above bandgap photons is a promising approach to overcome the detailed balance limit for higher solar cell efficiencies. However, this remains very challenging for 2D layered halide perovskites as the fast excess energy loss competes effectively with charge extraction. Herein, the authors engineer the energy cascade manifold of quantum well (QW) states in quasi‐2D Ruddlesden–Popper perovskites by facile tuning of the organic spacer to decelerate the energy loss. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 61 publications
3
34
0
Order By: Relevance
“…In the ground state, the calculated DFT structures of Dp 15 and Dm ( diasteroisomer) (Figures S12-S13, Tables S4-S6) afford identical dihedral angles of 30º within the bridging ligand, both strongly deviated from planarity. 3 MLCT(bpy) states in Dp (which are not observed experimentally but exist) and Dm are also expected to have similar dihedral angles of 30º, because the bridging ligands are present in their non-reduced forms like in the ground state.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the ground state, the calculated DFT structures of Dp 15 and Dm ( diasteroisomer) (Figures S12-S13, Tables S4-S6) afford identical dihedral angles of 30º within the bridging ligand, both strongly deviated from planarity. 3 MLCT(bpy) states in Dp (which are not observed experimentally but exist) and Dm are also expected to have similar dihedral angles of 30º, because the bridging ligands are present in their non-reduced forms like in the ground state.…”
Section: Resultsmentioning
confidence: 98%
“…It is therefore of paramount importance to tame these dissipative pathways for efficient and optimal solar energy conversion schemes. To this end, dissipative processes in singlet fission 2 or in hot carrier solar cells 3 were previously explored. Ultimately, photosynthesis was re-wired to promote electron extraction directly from photoexcited photosystems, avoiding the electron transfer reaction chain which dissipates energy.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular chromophores with retarded IC are analogous to hot carrier materials, where the excess energy of hot carriers can be extracted before cooling (heat transfer to the lattice) to band edge energies. 55 The next step is the development of molecular chromophores where IC is further retarded to the nanosecond timescale, compatible with bimolecular reactivity. Integration of these molecules and materials in anti-dissipation solar energy conversion schemes is a promising strategy to increase conversion efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…27−29 In this context, slow IC in the form of ILET or other electron transfers is very rare. For example, Huijser et al recently reported the population of two relaxed 3 MLCT excited states that behaved independently, implying a slow interconversion after incomplete ILET that takes 20 ps. 30,31 Our attention was focused on D p and D m (Figure 2), which are {Ru(bpy) 3 } dimers with outstanding properties in terms of light absorption, photostability, 32,33 and photoredox catalytic activity.…”
Section: ■ Introductionmentioning
confidence: 99%